RNA interference to reveal roles of β-Nacetylglucosaminidase gene during molting process in Locusta migratoria - Rong, Shuo; Li, Daqi; Zhang, Xueyao; Li, Sheng; Zhu, Kun Yan; Guo, Yaping; Ma, Enbo; Zhang, Jianzhen (My University, 2013)
β-N-acetylglucosaminidases are crucial enzymes involved in chitin degradation in insects. We identified a β-N-acetylglucosaminidase gene (LmNAG1) from Locusta migratoria. The full-length cDNA of LmNAG1 consists of 2667 nucleotides, including an open reading frame (ORF) of 1845 nucleotides encoding 614 amino acid residues, and 233- and 589-nucleotide non-coding regions at the 5’- and 3’-ends, respectively. Phylogenetic analysis grouped the cDNA-deduced LmNAG1 protein with the enzymatically characterized NAGs in group I. Analyses of stage- and tissue-dependent expression patterns of LmNAG1 were carried out by real-time quantitative PCR. Our results showed that LmNAG1 transcript level in the integument was significantly high in the last two days of the fourth and fifth-instar nymphs. LmNAG1 was highly expressed in foregut and hindgut. RNA interference of LmNAG1 resulted in an effective silence of the gene and a significantly reduced total LmNAG enzyme activity at 48 and 72 h after the injection of LmNAG1 dsRNA. As compared with the control nymphs injected with GFP dsRNA, 50% of the dsLmNAG1 injected nymphs were not able to molt successfully and eventually died. Our results suggest that LmNAG1 plays an essential role in molting process of L. migratoria.
Citation: Rong, S., Li, D., Zhang, X., Li, S., Zhu, K. Y., Guo, Y., . . . Zhang, J. (2013). RNA interference to reveal roles of β-N-acetylglucosaminidase gene during molting process in Locusta migratoria. Retrieved from http://krex.ksu.edu
Keywords: Locusta migratoria; Chitin degradation; β-N-acetylglucosaminidase; RNAi